Kinematics of judo breakfall for Osoto-Gari - Koshida, S.; Ishii, T.; Matsuda, T.; Hashimoto, T. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to identify kinematic parameters of breakfall for osoto-gari that can be distinguished between the experienced and the novice judokas. Eight experienced and four novice judukas volunteered to participate in the study. The motion data of the breakfall for osoto-gari were collected with a three-dimensional motion analysis technique. Our result demonstrated that there are significant differences in the hip movement pattern between the experienced and the novice judokas (p<0.05). In addition, the angle-time pattern of neck was also statistically different between the two groups; however, the difference of the angle pattern of the neck was not as meaningful as that of the hip. Our result suggests that judo coaches need to focus more on having novice judokas maintain the posture so that they will improve the breakfall skill effectively.